250 Delirium, Common but Forgotten. (16th September 2019) - Smyth, Hannah; Mahmood, Maham; Feely, Owen; Beirne, Joanna; Gallagher, Conal; O'Keeffe, Hannah; Walsh, Michael; Thomas, Niju; Rashid, Marwah; Khalil, Imran; Ansari, Ali Al; Shibani, Almaqdad Al; et al.
Abstract: Background: Delirium is a medical emergency prevalent amongst hospitalised older patients and associated with prolonged hospital stay, functional and cognitive decline, institutionalisation and increased mortality. In Irish hospitals, multiple strategies, e-learning courses, delirium guidelines and prevention programs have aimed to improve delirium care with better diagnosis and prevention. With the increasing awareness campaigns, we aimed to review the prevalence, screening and management of delirium in our cohort of older patients. Methods: A review of medical notes of all patients admitted under medical teams to an acute geriatric ward was carried out. Data was collected over a 3 week period in an Irish model 3 hospital. The following information was obtained from medical records: 1) Previous diagnosis of delirium/dementia 2) Documentation of a diagnosis of delirium 3) Features of delirium 4) Development of delirium as an inpatient 5) Formal screening for delirium 6) Cause and management of delirium 7) Length of stay. Results: Of 79 consecutive admissions to an acute geriatric ward (mean age 81.4, 57% female, 30% previous history of delirium or dementia), 25% (n=20) had a diagnosis of delirium documented. 22% (n=18) of patients had confusion and features of delirium highlighted but no formal diagnosis of delirium made during their inpatient stay. A further 20% (n=16) developed delirium on admission. Only 2.5% (n=2) of admissions had formal screening for delirium with the 4AT. 27.5% (n=11) of patients with delirium had a cause and management plan recorded. 70% (n=28) of patients with delirium had a length of stay of over 15 days. Conclusion: This review showed delirium recognition, screening, prevention and management were overlooked to an alarming extent in our cohort of older patients. The next step is introduction of the 4AT screening tool and regular education sessions to increase the awareness of delirium amongst medical teams looking after older patients and improve care and outcomes.